Analysis of Sharia MSME Financial Knowledge in Kuningan, West Java - Sondari, Endang; Yohanna, Larisa; Suseno, Imam (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the factors inhibiting the interest of the Kuningan, West Java society, in applying for financing to sharia MSMEs. This research uses field research with a qualitative approach. The types of data used in this study are primary data and secondary data. Data collection techniques are through observation, giving questionnaires, and documentation. The population in this study is the community of Kuningan, West Java, which includes the general public and owners businesses in the area. The results of the research on the background of the community not applying for financing are the lack of public knowledge of the existence of sharia SMEs, and the lack of socialization about sharia SMEs. The inhibiting factors for public interest in applying for financing at Islamic banks are the distance of Islamic banking locations, collateral, lack of socialization, different perceptions of sharia MSMEs for each individual.